THE IMPACT OF VISUAL AND AUDITORY LEARNING STYLES IN INSTRUCTIONAL VIDEOS FOR ENGLISH LANGUAGE LEARNERS - Magfirah; Eny Syatriana; Yassir Mallapiang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find information about the impact of visual and auditory learning in instructional videos on English Language Education students at Universitas Muhammadiyah Makassar. This research examining students' perspectives on the impact of visual and auditory learning in instructional videos based on their experiences. The subjects of this research are second semester students of English Education in the academic year 2023/2024 at Universitas Muhammadiyah Makassar who were selected using purposive sampling technique. Data were collected and analyzed using a qualitative approach. The instrument used to collect data is interview. The data were analyzed based on the interview results and made conclusions about the impact of visual and auditory learning in learning videos based on students' experiences. This research is expected to provide benefits for students in learning English. The results of this research indicate that visual learning styles have more positive impacts on students than auditory learning styles because students will more easily understand the material if it is presented in visual form. In addition, students also feel interested and enthusiastic and are not bored in participating in learning. it is evident from 13 or 100% of the subjects that 7 or 54% of the subjects apply a visual learning style, 4 or 30.7% of the subjects apply an auditory learning style and 2 or 15.3% of the subjects apply both. it means that students apply more visual learning styles than auditory learning styles.